Assessing the implementation of sustainable public procurement using quantitative text-analysis tools: A large-scale analysis of Belgian public procurement notices - Grandia, J. (Jolien); Kruyen, P.M. (Peter) (Journal of purchasing and supply management, 2020)
Public organizations are using sustainable public procurement (SPP) as a policy tool to address societal and environmental issues. Having a policy on SPP however does not guarantee implementation. Several barriers have for example been identified that prevent public procurers from implementing SPP in their procurement projects, such as financial constraints, lack of knowledge or motivation. The question therefore arises how much SPP public organizations actually implement in their procurement projects. However, existing studies often focus on the environmental part of SPP and often rely on using interviews or surveys to assess the perceived degree of SPP (which have been accused of being subject to social desirability bias and low response rates). Little is therefore known about what SPP is in practice, and how frequently it is implemented. In this study, we therefore provide a detailed operationalization of SPP that encompasses the full concept. We subsequently assess the implementation of SPP in practice using text mining techniques to analyse over 140.000 Belgian public procurement notices that were published between 2011 and 2016. The research shows that in more than 70% of the notices (with an annex) SPP is implemented, but there appears to be a downward trend. It seems that SPP is implemented less over time, rather than more. Environmentally friendly procurement was, relative to other types of SPP, prevalent over time and across regions. For SPP to live up to its potential there are thus still barriers to be overcome. •Sustainable public procurement (SPP) is, in practice, an umbrella concept that encompasses seven main categories.•Text-mining techniques were used to identify SPP in 144,749 Belgian public procurement notices.•Between 2011 and 2016 more than 70% of Belgian procurement notices (with an appendix) implemented SPP.•Environmentally friendly procurement is the most frequently implemented SPP category, innovation-oriented procurement the least.•Over time the implementation of SPP increased and then decreased.